HAMBATAN-HAMBATAN DALAM PENYELESAIAN PROYEK AKHIR MAHASISWA PROGRAM D3 DI JURUSAN KK FT UNP - YUSUF, SISKA; syafri, haswita; rahmiati, rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aims to determine the obstacles to completing the final project students D3 programs in the Department of KK FTUNP. Focus in this study are the barriers in determining ideas / topicof the final project, obstacles in the title of the final projectsubmission procedures and obstacles in the process of counseling.This type of research is descriptive qualitative. Data collectiontechniques in this study using observation, interview anddocumentation. Mechanical extension of the validity of the data withobservations, increased persistence and triangulation. Resultsshowed students encounter in determining ideas / topics related tothe difficulty of the final project students get useful ideas, creativeand innovative. Barriers associated with the procedure to befollowed by students in proposing ideas / topics is the difficulty ingetting approval ideas / topics submitted from faculty advisors andacademic advisor often do not agree that the idea / topic raisedfrequently replaced. Barriers related to the counseling process withfaculty mentors, students collided with a lot of the problemsassociated with scheduling the guidance of faculty mentors, studentsdo not understand the advice and guidance given due to lack ofability to mentor students in grammar writing scientific papers, thelack of student interest in reading as well as hard to find literatureBarriers average student in the following competencies inmanufacturing women's clothing considered quite. Keywords: barriers, the final project, D3 programs in theDepartment of Family Welfare